Taxonomic changes in Synanthedonini from Madagascar, with description of two new genera and species (Lepidoptera: Sesiidae) - Bartsch, Daniel (Zootaxa, 2018)
A checklist of the Synanthedonini of Madagascar is presented. The following taxonomic changes are suggested: Malgassesia pauliani Viette, 1955 syn. nov. is a junior synonym of Rodolphia hombergi Le Cerf, 1911a; Malgassesia biedermanni Viette, 1982 syn. nov. is a junior synonym of Malgassesia rufescens Le Cerf, 1922; Epitarsipus Le Cerf, 1922 stat. rev. is resurrected from the synonymy with Malgassesia Le Cerf, 1922, the earlier consisting of the single species E. rufithorax Le Cerf, 1922 comb. rev. The taxonomic position of three species, which were originally described in Chamaesphecia Spuler, 1910 and later excluded from this genus as “incertae sedis”, remains unclear. These species are here transferred to Malgassesia: M. andrianony Viette, 1982 comb. nov.; M. lemur Le Cerf, 1957 comb. nov.; and M. ferdinandi nom. nov., a replacement name for Ch. seyrigi Le Cerf, 1957. Two new species and genera of Synanthedonini, Cinctosesia polistiformis and Nesosphecia mystica gen. nov. et sp. nov., are described from a submontane rainforest in the vicinity of Andasibe in the East of Madagascar.